2015
DOI: 10.1073/pnas.1505410112
|View full text |Cite
|
Sign up to set email alerts
|

Increased size and cellularity of advanced atherosclerotic lesions in mice with endothelial overexpression of the human TRPC3 channel

Abstract: In previous in vitro studies, we showed that Transient Receptor Potential Canonical 3 (TRPC3), a calcium-permeable, nonselective cation channel endowed with high constitutive function, is an obligatory component of the inflammatory signaling that controls expression of the vascular cell adhesion molecule-1 (VCAM-1) and monocyte adhesion to coronary artery endothelial cells. Also, TRPC3 expression in these cells was found to be up-regulated by proatherogenic factors, which enhanced inflammation and VCAM-1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…Our previous studies demonstrating that in HCAECs TRPC3-mediated constitutive Ca 2+ influx is obligatory within the inflammatory signaling that controls expression of VCAM-1 and monocyte adhesion to these cells (Smedlund et al, 2010; Smedlund and Vazquez, 2008) revealed potential pathophysiological relevance of the constitutive function of this TRPC. The in vivo relevance of these findings was indeed validated by recent studies in Apoe knockout mice with endothelial-specific overexpression of human TRPC3 (Smedlund et al, 2015). In these mice, advanced atherosclerotic lesions in the aortic sinus were of bigger size, increased cellularity and exhibited augmented endothelial inflammation compared to lesions in non-transgenic mice (Smedlund et al, 2015).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our previous studies demonstrating that in HCAECs TRPC3-mediated constitutive Ca 2+ influx is obligatory within the inflammatory signaling that controls expression of VCAM-1 and monocyte adhesion to these cells (Smedlund et al, 2010; Smedlund and Vazquez, 2008) revealed potential pathophysiological relevance of the constitutive function of this TRPC. The in vivo relevance of these findings was indeed validated by recent studies in Apoe knockout mice with endothelial-specific overexpression of human TRPC3 (Smedlund et al, 2015). In these mice, advanced atherosclerotic lesions in the aortic sinus were of bigger size, increased cellularity and exhibited augmented endothelial inflammation compared to lesions in non-transgenic mice (Smedlund et al, 2015).…”
Section: Discussionmentioning
confidence: 65%
“…The in vivo relevance of these findings was indeed validated by recent studies in Apoe knockout mice with endothelial-specific overexpression of human TRPC3 (Smedlund et al, 2015). In these mice, advanced atherosclerotic lesions in the aortic sinus were of bigger size, increased cellularity and exhibited augmented endothelial inflammation compared to lesions in non-transgenic mice (Smedlund et al, 2015). …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…3.1 above, we discussed the evidence that demonstrated that in HCAECs the endogenous TRPC3 channels mediate constitutive calcium infl ux and are obligatory for proper operation of infl ammatory signaling through the NFkB pathway [ 25 , 27 ]. The in vivo relevance of these fi ndings was validated in recent studies using Apoe knockout mice with endothelial-specifi c overexpression of human TRPC3 [ 62 ]. Whereas early lesions -10 weeks on high fat diet-in the aortic root were not different from control animals, advanced plaques -16 weeks on high fat diet-in the transgenic mice were larger and of increased cellularity compared to non-transgenic mice.…”
Section: Effects Of Endothelial-specifi C Overexpression Of Trpc3mentioning
confidence: 76%
“…However, TRPC3 is also expressed in the other two major plaque cell types namely, smooth muscle (SMC) and endothelial (ECs) cells [ 4 , 5 ]. Atherorelevant functions of TRPC3 in SMCs, if any, are not known and recent work from our laboratory shows that in vivo, TRPC3 supports infl ammation in endothelial cells ( [ 62 ] and Sect. 5.2 below).…”
Section: Above)mentioning
confidence: 99%